PEMANFAATAN BUAH TIN UNTUK PEREKONOMIAN DAN KESEHATAN - Enjang Suherman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Buana Perjuangan Karawang, 2019)
The natural wealth of Medalsari is mostly plantations. Many extensive plantation areas at the south of Karawang are shady forests. Not comparable with less than optimal yields due because low prices, marketing and other problems. The purpose of this service is